2018
DOI: 10.4073/csr.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Small class sizes for improving student achievement in primary and secondary schools: a systematic review

Abstract: This Campbell systematic review examines the impact of class size on academic achievement. The review summarises findings from 148 reports from 41 countries. Ten studies were included in the meta‐analysis. Included studies concerned children in grades kindergarten to 12 (or the equivalent in European countries) in general education. The primary focus was on measures of academic achievement. All study designs that used a well‐defined control group were eligible for inclusion. A total of 127 studies, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 189 publications
0
34
0
2
Order By: Relevance
“…The result of this study is supported by DeMonbrun et al (2017) that states learning achievement is obtained due to the selection of appropriate and quality learning methods. If the teacher can apply the learning method correctly and precisely depends on the needs in class, it brings a positive impact on improving student learning achievement at school (Filges et al, 2018;Yang et al, 2020). One favorite method for students is the discussion method.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study is supported by DeMonbrun et al (2017) that states learning achievement is obtained due to the selection of appropriate and quality learning methods. If the teacher can apply the learning method correctly and precisely depends on the needs in class, it brings a positive impact on improving student learning achievement at school (Filges et al, 2018;Yang et al, 2020). One favorite method for students is the discussion method.…”
Section: Discussionmentioning
confidence: 99%
“…The program features implemented in MPS—including relatively small class sizes, robust professional development, best practices sharing among instructors, and networking and relationship building between teachers and students across classrooms and outside the school day to cultivate presence—appeared to contribute to positive overall experiences for students and teachers in telepresence courses (Filges, Sonne-Schmidt, & Nielsen, 2018; Van Driel & Berry, 2012). Without these features, such positive results would likely not have been possible.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, investigating the same study sample, found no relationship [ 34 , 35 ], while another study found a relationship but did not define the direction of the relationship [ 48 ]. Previous research suggests that a higher number of students in a class might be related to poorer motor skills, because the available resources such as space to move around and teachers’ time and attention are more diluted [ 58 , 80 ]. However, a review has shown that the effect of class size on other domains such as academic achievement is small at best [ 80 ].…”
Section: Discussionmentioning
confidence: 99%